(3GdVeGfGJ GdJTQjYjI ddGSJKeGQGJ GdCLfHjI (B:s (3OQGSI ebGQfI (B/s - (3gQhQj, TjQRGO MejOs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2018)
(3jJfGhd cJGH (B((3GdVeGfGJ GdJTQjYjI ddGSJKeGQGJ GdCLfHjI (B: (3OQGSI ebGQfI(B) (3GdPj bGe HJCdjag O(B. (3TjQRGO MejO gQhQj aj MhGdj (B(498) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdVeGfGJ GdJTQjYjI ddGSJKeGQGJ GdCLfHjI(B) (3eSJYQVG GdehVhYGJ GdJGdjI (B: (3GdebOeI, GdHGH GdJegjOj, eGgjI GdVeGfGJ GdJTQjYjI aj GdGSJKeGQGJ GdCLfHjI, GdaUd GdChd (B: (3eGgjI GdGSJKeGQ GdCLfHj hCfhGYg, GdeHMK GdChd (B: (3JYQja GdGSJKeGQ GdCLfHj, GdeHMK GdKGfj (B: (3CfhGY GdGSJKeGQ GdCLfHj, GdaUd GdKGfj (B: (3eGgjI GdVeGfGJ GdJTQjYjI aj YbO GdGSJKeGQ GdCLfHj, GdeHMK GdChd (B: (3eaghe GdVeGfGJ GdJTQjYjI, GdeHMK GdKGfj (B: (3GdbjeI GdbGfhfjI ddVeGfGJ GdJTQjYjI aj YbO GdGSJKeGQ GdCLfHj, GdHGH GdChd (B: (3CMcGe hVeGfGJ GdGSJKeGQGJ GdCLfHjI, GdaUd GdChd (B: (3GdeRGjG hGdVeGfGJ GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdeHMK GdChd (B: (3GdeRGjG GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdeHMK GdKGfj (B: (3GdVeGfGJ GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdaUd GdKGfj (B: (3GdEYaGAGJ hGdJSgjdGJ GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdeHMK GdChd (B: (3GdEYaGAGJ GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdeHMK GdKGfj (B: (3GdJSgjdGJ GdbGfhfjI ddGSJKeGQGJ GdCLfHjI, GdaUd GdKGdK (B: (3Mbhb hGdJRGeGJ GdeSJKeQ GdCLfHj, GdHGH GdKGfj (B: (3VeGfGJ JShjI efGRYGJ GdGSJKeGQ, GdaUd GdChd (B: (3GdVeGfGJ GdbVGFjI dJShjI efGRYGJ GdGSJKeGQ, GdaUd GdKGfj (B: (3GdVeGfGJ GdOhdjI dJShjI efGRYGJ GdGSJKeGQ, GdaUd GdKGdK (B: (3VeGfGJ GdJMcje dJShjI efGRYGJ GdGSJKeGQ, GdNGJeI, bGFeI GdeQGLY(B.s
(3HHdjhLQGajI (B: (3UaMI (B467-496.s
Keywords: (3GdGSJKeGQGJ GdCLfHjIs -- (3bhGfjf hJTQjYGJs; (3GdbGfhf GdOhdj GdGbJUGOjs; (3GdGSJKeGQ GdOhdjs